2006
DOI: 10.1093/ajcn/83.6.1505s
|View full text |Cite
|
Sign up to set email alerts
|

n−3 Polyunsaturated fatty acids, inflammation, and inflammatory diseases

Abstract: Inflammation is part of the normal host response to infection and injury. However, excessive or inappropriate inflammation contributes to a range of acute and chronic human diseases and is characterized by the production of inflammatory cytokines, arachidonic acid-derived eicosanoids (prostaglandins, thromboxanes, leukotrienes, and other oxidized derivatives), other inflammatory agents (eg, reactive oxygen species), and adhesion molecules. At sufficiently high intakes, long-chain nҀ3 polyunsaturated fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,503
12
53

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,104 publications
(1,602 citation statements)
references
References 160 publications
(139 reference statements)
34
1,503
12
53
Order By: Relevance
“…The primary cellular origin of IL‐1β in atherosclerosis is unclear, but we have previously shown in coronary atherosclerotic plaques of patients with IHD that IL‐1β is predominantly expressed in relatively large amounts in the endothelium and vasa vasorum 75. We did show robust reductions in IL‐8, RANTES, and MCP‐1 in plasma, although previous animal studies have reported no significant correlation between DHA feeding and these plasma cytokines 76. Most of these studies, however, were small and used fish oil, with little attention given to specific DHA effects.…”
Section: Discussioncontrasting
confidence: 54%
“…The primary cellular origin of IL‐1β in atherosclerosis is unclear, but we have previously shown in coronary atherosclerotic plaques of patients with IHD that IL‐1β is predominantly expressed in relatively large amounts in the endothelium and vasa vasorum 75. We did show robust reductions in IL‐8, RANTES, and MCP‐1 in plasma, although previous animal studies have reported no significant correlation between DHA feeding and these plasma cytokines 76. Most of these studies, however, were small and used fish oil, with little attention given to specific DHA effects.…”
Section: Discussioncontrasting
confidence: 54%
“…In line with this finding, the PUFA composition of cell membranes is dependent on the dietary intake to a great extent. It has been shown, for instance, that when humans ingest fish products, the n-3 PUFAs EPA and DHA from the diet partially replace the n-6 PUFAs, especially AA, in cell membranes [14,15].…”
Section: Figurementioning
confidence: 99%
“…[11,34,117]. PGE 2 , an AA metabolite, has also been shown to stimulate IL-6 production [15]. There is in vitro evidence of cross-talk between the COX-2/PGE 2 and IL-6 systems [118] in murine osteoblast-osteoclast co-cultures that results in increased osteoclastogenesis via effects on the RANK/RANKL/OPG system.…”
Section: Effects Of Polyunsaturated Fatty Acids and Metabolites On Cymentioning
confidence: 99%
“…There is strong evidence for health benefits of these fatty acids, especially with regard to CVD (33)(34)(35)(36) . They act to modify tissue and blood lipid metabolism, blood lipid concentrations, blood coagulation, immune function, inflammation and endothelial function (37)(38)(39)(40)(41) . EPA and DHA are readily incorporated into cells and tissues and act to modify membrane properties, eicosanoid profiles, signal transduction processes and gene expression (11,12) .…”
Section: Desirable Properties For Lipids To Be Used In Artificial Nutmentioning
confidence: 99%